2019
DOI: 10.1016/j.jddst.2019.101194
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive paclitaxel-loaded chitosan-poly (isobutyl cyanoacrylate) core-shell nanocapsules containing copaiba oil designed for oral drug delivery

Abstract: The development of drug delivery systems for potent anticancer drugs like paclitaxel remains a challenger. The aim of this work was to study the mucoadhesive properties of paclitaxelloaded chitosan-poly (isobutyl cyanoacrylate) core-shell nanocapsules designed for oral drug delivery. Using an experimental design approach, the nanocapsules were produced and, then, physicochemically characterized. Mucoadhesion assays were performed in-vitro by the aggregation test with mucin and ex-vivo, in Ussing Chamber, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…However, there is little discussion regarding the quantitative measurement of the polymeric shell of nanocapsules in most of studies; only few examples can be here reported. The main characterization method of the thickness is observation via transmission electron microscopy (TEM) [ 47 , 148 ]. For example, a 10-nm polymeric shell has been qualitatively estimated by TEM from argon oil/oleoyl polyoxylglycerides/Eudragit ® RS nanocapsules [ 176 ].…”
Section: Challenge Of Nanocapsules As Drug Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is little discussion regarding the quantitative measurement of the polymeric shell of nanocapsules in most of studies; only few examples can be here reported. The main characterization method of the thickness is observation via transmission electron microscopy (TEM) [ 47 , 148 ]. For example, a 10-nm polymeric shell has been qualitatively estimated by TEM from argon oil/oleoyl polyoxylglycerides/Eudragit ® RS nanocapsules [ 176 ].…”
Section: Challenge Of Nanocapsules As Drug Delivery Systemmentioning
confidence: 99%
“…In this case, to store nanocapsules into dried form is generally preferable to improve the stability of nanocapsules and also prolong the store term [ 183 ]. Moreover, to adapt preparations of particular pharmaceutical dosage forms, such as oral tablet, it is necessary to manufacture the polymeric nanocapsules suspension into dry state for further preservation and usage [ 129 , 148 , 184 ]. Spray drying as one of the common drying method has been applied for recovery of nanocapsules into solid dry state.…”
Section: Challenge Of Nanocapsules As Drug Delivery Systemmentioning
confidence: 99%
“…These characteristics include: slight burst release of drug in the early phase; easy permeability; resistance to degradation; hydrophobicity; high surface charge; high drug loading; nontoxic nature; high binding as well as deep permeating ability through mucous membrane owing to their nanosize [ 10 , 11 , 12 , 13 ]. Several polymers such as alginate and chitosan (CH) [ 14 ] have been exploited not only for their mucoadhesive effect in GI but also for discovering their probable effectiveness in the colon milieu.…”
Section: Introductionmentioning
confidence: 99%
“…CH is a cationic polysaccharide, which rapidly affixes to mucous membrane with a negative surface charge [ 14 ]. It is a biodegradable polymer and exhibits minimum toxicity, which make it an ideal carrier for the delivery of several drugs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel (PTX) is a diterpenoid pseudoalkaloid anticancer drug extracted from the Pacific Yew tree Taxus brevifolia [ 6 ]. Its chemotherapeutic effect is associated with its ability to bind to tubulin promoting microtubule assembly, stabilizing the existing microtubules and enhancing the action of tubulin dimers, therefore inhibiting their disassembly.…”
Section: Introductionmentioning
confidence: 99%